POVERTY DYNAMICS IN INDONESIA, 2008â20101 - Astuti, Avi Novia; Asra, Abuzar; Ilmma, Amri (RIEBS, 2012)
Although official figures show that poverty in Indonesia has declined, it remains one of the keydevelopment issues. The current static poverty approach in assessing poverty changes has not been sufficientto design effective and strategic policies for poverty reduction. This study analyses the dynamicsof poverty in Indonesia using the 2008â2010 panel data of the Survei Sosial Ekonomi Nasional(Susenas), the National Socio-Economic Survey. This study uses a sequential transition matrix to depictthe dynamics of poverty that are shown by the magnitude of changes in poverty status (especially transientand chronic poverty). The matrix indicates that the incidence of transient and chronic povertyfor the period 2008â2010 was 23.2 per cent, much higher than the figure of 13.3 per cent derivedby using the static poverty approach in 2010. This suggests that the magnitude of the poverty problemin Indonesia is indeed much higher than the common perception that is based on the usual povertyindicators. The results of a multinomial logistic model reconfirm the importance of investment ineducation, improvement in the agricultural and non-agricultural sectors, and reduction of dependencyratios to help cope with transient and chronic poverty. To help develop poverty alleviation policy andto design intervention programs, using the statistics of chronic poverty and the Human DevelopmentIndex, there are eight provinces that could be considered as the core focus area. These provinces areNangroe Aceh Darussalam, Lampung, East Java, East Nusa Tenggara, Central Sulawesi, South EastSulawesi, Maluku, and West Papua, and all need immediate intervention and accelerated povertyreduction programs.Keywords: Geographical targeting, Multinomial logistic, Poverty dynamics, Transient and chronicpoverty, Sequential transition